Heritage, crisis, and community crime prevention in Nepal - Mackenzie, Simon (2018)
Following Nepal's 2015 earthquake there was speculation that sacred art would be looted from the ruins of severely damaged temples due to breakdown in formal security. Although pillage did not immediately occur, the months following the earthquake have seen the theft of sacred heritage items. As Nepali sacred art remains under threat of theft, we explore the processes by which government intervention can be destructive of the community dynamic that maintains local crime prevention on an informal and unofficial level. Can situational crime prevention measures when imposed in a top-down fashion upon communities by state actors be corrosive of collective efficacy, and therefore ultimately self-defeating in crime prevention terms? The case of post-quake Nepal seems to suggest that the answer to this question is, in some circumstances, yes